Perancangan Ulang Tata Letak Fasilitas Lantai Produksi PT. A Menggunakan Simulasi Software Flexsim - Alfian Julianto; Dina Rachmawaty; Ade Yanyan Ramdhani (Industrika : Jurnal Ilmiah Teknik Industri, 2023)
PT. A found to have lost time production problems due to rain so that it was not possible to transport the transfer of materials. It can be concluded that the recommended layout is the proposed layout 2 where the total distance and moment of material handling per month is known to be the difference from the simulation of the initial model layout of 97 meters from the total initial distance and the difference in the moment of material handling in a month of 2,089 meters from the initial material handling moment with the addition of cover facilities for all material handling lines so that in any weather the material handling transportation process between departments is not disturbed. In the output results obtained using the FlexSim software simulation proposal 2, where all output products are above the number of initial simulation outputs and proposal 1 where the number of outputs is known to be 418,224, 144,695, 120,677, 80,557, and 40,131. While the comparison of material handling costs explained earlier there was no decrease, but what happened instead was an increase in proposal 1 and proposal 2, but the increase was still said to be reasonable because the highest cost obtained in the simulation, namely in proposal 2 of IDR 2,307,431.00, was still below the employee's salary of IDR 2,340,000.00 which had been determined by the company. Keywords: ARC, ARD, lost time, OMH, software flexsim